Filipino prospective teachers’ experiences in teaching in K12 science curriculum: A cross-sectional research - Ace Mark R. Antipolo; Danilo V. Jr Rogayan (University of Muhammadiyah Malang, 2021)
The K12 science curriculum in the Philippines uses spiral progression which is a concept of learning approach where students revisit the same topics throughout their school career that increases complexity and reinforcement of previous learning. This cross-sectional study determined the experiences of Filipino prospective science teachers (PSTs) specializing in biology and physical science in teaching in the K12 science curriculum with emphasis of their challenges. The respondents of this study were 30 PSTs in five teacher education institutions (TEIs) in Central Luzon, Philippines. Results revealed that the PSTs rarely experience teaching challenges in the K12 science curriculum in terms of content knowledge and pedagogy, learning environment, diversity of learners, curriculum and planning, assessment and reporting, community linkages and professional engagement, and in personal growth and professional development. No significant differences were noted in the challenges of PSTs when grouped according to profile variables. A positive significant moderate to high correlations were noted between and among the challenges variables. The study suggests that the administration continuously spearhead in-house seminars and equip prospective teachers with innovative teaching strategies. TEIs may also consider curriculum review to align the course syllabi in the teacher education curriculum to the Department of Education curriculum. Schools may further evaluate the policies, standards, and guidelines of the teacher education curriculum to make the science education degree programs relevant.